2021
DOI: 10.1016/j.imlet.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 producing B cells regulated 1,3-β-glucan induced Th responses in coordinated with Treg

Abstract: Background: Repeated exposure to fungi contaminated dust can lead to multiple adverse effect on lung, such as hypersensitivity pneumonitis, granuloma even irreversible brosis. 1,3-β-glucan, as the major cell wall component of fungi, was considered as its exposure biomarker. Existing studies showed that series of Th response were involved in 1,3-β-glucan induced hypersensitivity pneumonitis, in which macrophages, regulatory T cells (Treg) and IL-10 producing B cells were reported to participate. The reciprocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…To elucidate the regulatory mechanism of IL-10 producing B cells in Th and Treg, an IL-10 producing B cell deficient mouse model was generated by intraperitoneal injection of anti-CD22 antibody. The results confirmed that IL-10 producing B cells can modulate the 1,3-β-glucan-induced inflammatory response [40].…”
Section: Discussionsupporting
confidence: 69%
“…To elucidate the regulatory mechanism of IL-10 producing B cells in Th and Treg, an IL-10 producing B cell deficient mouse model was generated by intraperitoneal injection of anti-CD22 antibody. The results confirmed that IL-10 producing B cells can modulate the 1,3-β-glucan-induced inflammatory response [40].…”
Section: Discussionsupporting
confidence: 69%